RURAL-TO-URBAN AND CITY-TO-CITY MIGRATIONS IN KAZAKHSTAN: MOTIVES AND RESULTS - ZABIROVA, Aygul (CENTRAL ASIA AND THE CAUCASUS, 2004)
The problem of migration is one of those that make it possible to better understand the trends and repercussions of what has been going on in post-Soviet Kazakhstan. The following aspects of migration are most important: emigration of the Russian speakers; repatriation of ethnic Kazakhs, and movement of rural Kazakh population to cities. So far, academic writings have failed to pro-vide an adequate interpretation of the theoretical side of the migration problem. At the empirical level, however, several research projects have been realized or are being carried out. As a rule, all of them analyze outside migrations caused by the Soviet Union’s disintegration. Working in our re-public our own and foreign academics concentrated on the outflow of Russian speakers, while completely neglecting the movement of the Kazakh population inside their republic. Meanwhile, internal migration (its scope, directions, economic and sociopolitical prerequisites and results) is as important as ever and has even acquired new significance because new causes of migration appeared side by side with the traditional ones. Economic reforms (including the transfer to market economy, private property and entrepreneurship) as well as a wider range of human rights served as an important impetus of rural-to-urban migration and provided le-gal support for the freedom of movement. Rural-to-urban migration is going along with accelerating city-to-city migration, mainly from the regional centers to the new and old capitals of Kazakhstan (Astana and Almaty).